Problematic questions and research-capacious technologies of structural identification of objects dynamic models according to full-scale investigation - Блохин, Л. H.; Держак, C. B. (Proceedings of National Aviation University (archive), 1999)
Proposed is an algorithm of structural identification of objects dynamic models according to natural Investigation data. Worked out is methodics of making structural identification with natural experiment. Determined are the requirements to picking up and processing experimental information. Worked out are programs for solution of problems of structural identification on personal computer. To illustrate the efficiency of structural identification algorithm we have chosen identification model of three dimensional dynamic stand as an example